Changes of right-hemispheric activation after constraint-induced, intensive language action therapy in chronic aphasia: fMRI evidence from auditory semantic processing1 - Mohr, Bettina; Difrancesco, Stephanie; Harrington, Karen; Evans, Samuel; Pulvermüller, Friedemann (Frontiers in Human Neuroscience, 2014)
The role of the two hemispheres in the neurorehabilitation of language is still under dispute. This study explored the changes in language-evoked brain activation over a two-week treatment interval with intensive constraint induced aphasia therapy (CIAT), which is also called intensive language action therapy (ILAT). Functional magnetic resonance imaging (fMRI) was used to assess brain activation in perilesional left hemispheric and in homotopic right hemispheric areas during passive listening to high and low-ambiguity sentences and non-speech control stimuli in chronic non-fluent aphasia patients. All patients demonstrated significant clinical improvements of language functions after therapy. In an event-related fMRI experiment, a significant increase of BOLD signals was manifest in right inferior frontal and temporal areas. This activation increase was stronger for highly ambiguous sentences than for unambiguous ones. These results suggest that the known language improvements brought about by intensive constraint-induced language action therapy at least in part relies on circuits within the right-hemispheric homologues of left-perisylvian language areas, which are most strongly activated in the processing of semantically complex language.